2017
DOI: 10.1111/1750-3841.13599
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lipid Content in a Corn Oil Preparation on the Bioaccessibility of β‐Carotene: A Comparison of Low‐Fat and High‐Fat Samples

Abstract: Some individuals with fat maldigestion have compromised digestive systems, which causes the incomplete hydrolyzation of ingested lipids within the gastrointestinal tract (GIT). We studied the influence of high-fat (20%) and low-fat (4%) contents on the bioaccessibility of a highly hydrophobic nutraceutical (β-carotene) through a simulated GIT model consisting of mouth, stomach, and small intestine phases. The low-fat and high-fat values were chosen to simulate low-fat and high-fat diets. The triglycerides in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The bioavailability of hydrophobic bioactives also depends on the total amount of digestible oil inside a delivery system [97,100]. If there is too little oil present, then there are not enough mixed micelles generated to solubilize all of the hydrophobic bioactives present.…”
Section: Oil Phase Concentrationmentioning
confidence: 99%
“…The bioavailability of hydrophobic bioactives also depends on the total amount of digestible oil inside a delivery system [97,100]. If there is too little oil present, then there are not enough mixed micelles generated to solubilize all of the hydrophobic bioactives present.…”
Section: Oil Phase Concentrationmentioning
confidence: 99%
“…Carotenoids can also be encapsulated into more traditional delivery systems like lipid-based nanocarriers [ 32 , 33 ]. The lipid-based nanocarriers include nanoemulsions [ 34 , 35 , 36 ], nanoliposomes [ 37 , 38 , 39 ], solid lipid nanoparticles [ 40 , 41 , 42 ], and nanostructured lipid carriers [ 43 , 44 , 45 ] ( Figure 2 ). A study by Tan and coauthors [ 38 ] found that the encapsulation of carotenoids in liposomes enhanced the antioxidant activity in different antioxidant models.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the presence of anionic free fatty acids generated from lipid digestion would also lead to a relatively high negative charge in the small intestinal phase. Similar trend in the ζ‐potential when the nanoemulsions moved from the stomach phase to the small intestinal phase was also reported by other authors (Zhang et al ., ; Xia et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Ergocalciferol-loaded nanoemulsions prepared using different emulsifiers were subjected to an in vitro digestion model that simulated the mouth, stomach and small intestinal phases. The in vitro digestion model applied in our current study was based on those reported previously, with minor modifications (Qian et al, 2012;Xia et al, 2017).…”
Section: In Vitro Digestionmentioning
confidence: 99%